ANALISIS PREVENTIVE MAINTENANCE MESIN INJECTION MOLDING DI PT YEAKIN PLASTIC INDUSTRY BATAM - Arnold Sihombing; Elsya Paskaria Loyda Tarigan (Computer Science and Industrial Engineering, 2024)
PT Yeakin Plastic Industry is a company engaged in manufacturing plastic goods. The problem that occurs in this study is the high downtime that occurs on the injection molding machine. So that the amount of production does not reach the target. The purpose of this study is to determine the interval of preventive maintenance injection molding to minimize machine downtime. The method used in this research is Reliability Centered Maintenance (RCM). From the results of the study, it was found that the results of the weibull distribution obtained the maintenance interval of the A200 injection molding machine with the longest downtime, where there were 11 breakdowns in 6 months, and maintenance actions were carried out at the maintenance interval for 100.55 hours. On the A201 injection molding machine there are 8 breakdowns in 6 months, and maintenance actions are carried out at maintenance intervals for 144.44 hours. On the A202 injection molding machine there were 8 breakdowns in 6 months, and maintenance actions were taken at the maintenance interval for 122.97 hours.